Ecological niche divergence between extant and glacial land snail populations explained - Horsák, Michal; Horsáková, Veronika; Divíšek, Jan; Nekola, Jeffrey C (Scientific reports, 2022)
The presence of Last Glacial Maximum (LGM) biotic communities without modern counterparts is well known. It is particularly evident in central European fossil LGM land snails whose assemblages represent an odd mix of species that are currently limited to either xeric or wetland habitats. Here we document a genetically verified discovery of the modern calcareous wetland species Pupilla alpicola on Iceland, where it is limited to dry grasslands. This species also represents a common European LGM fossil, and its new records from Iceland help explain puzzling shifts of some glacial land snails of xeric grassland habitats to open wetlands today. Similarities between the climates of modern Iceland and LGM Eurasia suggest that this species did not become limited to wetlands in continental Europe until after the Late Pleistocene-Holocene climate transition. These results are a strong reminder that assumptions of ecological uniformity must be questioned and that the quality and robustness of palaeoecological reconstructions is dependent upon adequate knowledge of the full autecological range of species over time.
Keywords: Ecosystem; Snails; zkameněliny; Fossils; mokřady; klimatické změny; pastviny; Climate; Population Dynamics; hlemýždi; zvířata; Animals; ekosystém; Island; Iceland; Grassland; Wetlands; podnebí; Climate Change; populační dynamika